Rancang Bangun Prototype Monitoring Banjir Berbasis Website - Anorgi, Andrew; Saragih, Agus Sehatman; Sari, Nova Noor Kamala (Journal of Information Technology and Computer Science, 2023)
Indonesia usually has certain areas where flooding occurs in different locations that can be flooded by rainfall that falls then will flow through the upstream of the river or the end of the river path where the water will pass and collect to a place where the water can accommodate is no longer available. again wasted water that there is no drain line. Based on these problems, a website-based flood monitoring prototype system is needed by adding the following functions IoT (Internet of Things) which can monitor floods about the condition of the water level graph on the website that can be seen by officers. This study uses an experimental method that was developed based on the needs of the research. In hardware system design used is microcontroller NodeMCU ESP8266 as system control. An ultrasonic sensor for water level and an anemometer to determine the current speed determines the water level in the box. Based on the research that has been carried out, the conclusion is that the system can predict when a flood will occur in the next few hours when water enters the box and the website graph appears. After the water is full it will send a notification via telegram bot to the owner of the officer within 3 minutes.